2005
DOI: 10.1177/1073274805012004s02
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Quality-of-Life Issues in Chinese Women with Breast Cancer: A Qualitative Investigation

Abstract: Little is known about the cultural beliefs and quality of life (QOL) of US-born and foreign-born Chinese women with breast cancer. We conducted individual semistructured qualitative interviews to explore the meaning of QOL, identify beliefs about cancer, and make comparison between US-born and foreign-born survivors. Women in this study identified the stigma of breast cancer that exists in the Asian community. They also described interpersonal support as central to a good QOL. However, when describing QOL, for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
82
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(88 citation statements)
references
References 30 publications
3
82
1
1
Order By: Relevance
“…In agreement with similar studies that documented numerous negative psychological consequences for breast cancer patients Daley et al 2004;Hewitt et al 2004;Wong-Kim et al 2005), we found that, when participants are faced with breast cancer diagnosis news, they will experience a variety of emotions such as fear, shock, disbelief, sadness, hostility, anger, depression, anxiety and other feelings of psychosocial distress. Depression and anxiety were the most prevalent psychological reactions in these patients; these feelings can interfere with a patient's ability to cope with illness and have a direct impact on her quality of life and psychological wellbeing.…”
Section: Discussionsupporting
confidence: 91%
“…In agreement with similar studies that documented numerous negative psychological consequences for breast cancer patients Daley et al 2004;Hewitt et al 2004;Wong-Kim et al 2005), we found that, when participants are faced with breast cancer diagnosis news, they will experience a variety of emotions such as fear, shock, disbelief, sadness, hostility, anger, depression, anxiety and other feelings of psychosocial distress. Depression and anxiety were the most prevalent psychological reactions in these patients; these feelings can interfere with a patient's ability to cope with illness and have a direct impact on her quality of life and psychological wellbeing.…”
Section: Discussionsupporting
confidence: 91%
“…These fi ndings were consistent with those of previous studies [28,29] . In a study exploring the QOL of Chinese women with breast cancer, Wong-Kim et al [18] found that the signifi cant others was a source of primary support and an important factor when assessing QOL. Family members also played a significant role in a patient's decisionmaking process.…”
Section: Factors Infl Uencing the 5 Domains Of Qol Of Participantsmentioning
confidence: 99%
“…Numerous studies have examined the QOL and predictors of QOL among patients with breast cancer in Western populations. Studies of QOL in the Chinese breast cancer population, however, are limited [16][17][18] . Cui et al [16] investigated the long-term effects of medical and demographic factors on the QOL of 1,065 Chinese breast cancer survivors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, when compared to the Malay, Chinese men are only allowed to have one legal wife. According to Wong-Kim et al (2005), after being diagnosed with breast cancer, the Chinese women were more concerned about survival. Thus, these women put a greater emphasis on recuperating from their illness rather than worrying about body image and their marital relationship.…”
Section: Discussionmentioning
confidence: 99%